URANYL ACETATE SPECIATION IN AQUEOUS SOLUTIONS-AN XAS STUDY BETWEEN 25°C AND 250°C - Bailey E.H.; Mosselmans J.F.W.; Schofield P.F. (My University, 2004)
Speciation of uranium (VI) in acetate solutions between 25 and 250°C, at pH values between 1.8 and 3.8 and acetate/uranium (Ac/U) ratios of 0.5 to 100 has been investigated using uranium LIII-edge X-ray absorption spectroscopy. With increasing pH the UO2(Ac)20 species becomes more important than UO2(Ac)+ species, which is predominant below pH 2. It remains the dominant species as pH is further increased to 3.8 at an Ac/U ratio of 20. Decrease in U-Oeq bond distance and coordination number with increasing solution age indicates that steric/kinetic factors are important and that equilibrium is attained slowly in this system with initial acetate coordination to the uranyl ion being monodentate or pseudo-bridging before slow conversion to bidentate chelation. Acetate coordination to the uranyl ion appears to decrease as temperature is increased from room temperature to ∼100°C before increasing in solutions of Ac/U > 2. For solutions where Ac/U ≤ 2 at pH 2.1, there is no evidence for uranyl acetate speciation at low temperatures, but at elevated temperature bidentate uranyl-acetate ion-pairing is evident. The existence of the uranyl acetate species in the temperature range 200 to 240°C demonstrates the importance of including acetate and other organic ligands in models of uranium transport at elevated temperatures.